2021
DOI: 10.3390/children8110988
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation and Wellbeing Experience in Children with Special Needs during the COVID-19 Pandemic

Abstract: Social distancing due to the COVID-19 pandemic represented a golden opportunity to implement telerehabilitation for clinical groups of children. The present study aims to show the impact that telerehabilitation had on the experience of well-being of children with special needs being treated at the Foundation IRCCS Neurological Institute ‘C. Besta’ in Milan (Specific Learning Disorders and Cerebral Palsy diagnosis); it aims to do so by comparing it with experiences of those who did not undertake telerehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…A total of 5449 records were retrieved after removing duplicates; 39 were reviewed in full text. Here, we report findings from 19 studies on well-being interventions for children and youth (Table 2) [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Studies involved a total of 7492 children and youth and 954 parents, all of which occurred • Agency: has self-esteem; a sense of agency and of being empowered to make meaningful choices and to influence their social, political, and material environment; and capacity for self-expression and self-direction appropriate to their evolving capacities and stage of development • Identity: feels comfortable in their own self and with their identity(s), including their physical, cultural, social, sexual, and gender identity • Purpose: has a sense of purpose, desire to succeed, and optimism about the future • Resilience: equipped to handle adversities both now and in the future, in a way that is appropriate to their evolving capacities and stage of development • Fulfilment: feels that they are fulfilling their potential now and that they will be able to do so in the future during the first year of the COVID-19 pandemic (March 2020 to March 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 5449 records were retrieved after removing duplicates; 39 were reviewed in full text. Here, we report findings from 19 studies on well-being interventions for children and youth (Table 2) [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Studies involved a total of 7492 children and youth and 954 parents, all of which occurred • Agency: has self-esteem; a sense of agency and of being empowered to make meaningful choices and to influence their social, political, and material environment; and capacity for self-expression and self-direction appropriate to their evolving capacities and stage of development • Identity: feels comfortable in their own self and with their identity(s), including their physical, cultural, social, sexual, and gender identity • Purpose: has a sense of purpose, desire to succeed, and optimism about the future • Resilience: equipped to handle adversities both now and in the future, in a way that is appropriate to their evolving capacities and stage of development • Fulfilment: feels that they are fulfilling their potential now and that they will be able to do so in the future during the first year of the COVID-19 pandemic (March 2020 to March 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Chen and colleague's mindfulness meditation and aerobic exercise RCT resulted in decreased anxiety (on the Self-Rating Anxiety Scale) at 1-month follow-up [34] while the Philosophy for Children intervention and Mindfulness-Based Intervention conducted by Malboeuf-Hurtubise and colleagues improved anxiety symptoms (on the Behavior Assessment Scale for Children-3rd edition) for children at 1-week follow-up [43]; no decrease in anxiety nor depression symptoms were observed by the art therapy experiential interventions described in another included study [43]. The three-group telerehabilitation program conducted by Sarti and colleagues revealed that children with specific learning disorders and cerebral palsy scored higher than typically developing children in the Respect Scale (of the Comprehensive Inventory for Thriving Children) of well-being experience [45]. Compared to controls, the SSI Intervention deployed by Schlieder and colleagues reduced 3-month depressive symptoms (on the Children's Depression Inventory) and 3-month restrictive eating (measured using the Dietary Restriction Screener), while the Heartfulness Meditation and Brainwave Entrainment interventions by Yadav and colleagues decreased anger, improved mood, and decreased stress (on the Perceived Stress Scale, Patient Health Question-9, and the Profile of Mood States), but only for adolescents who received the 4-week Heartfulness Meditation intervention [48].…”
Section: Health and Nutrition Domainmentioning
confidence: 98%
See 3 more Smart Citations